2021
DOI: 10.3389/fbioe.2021.628129
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of Fibrous Collagen Dura Substitutes

Abstract: Dura substitutes are applied in duraplasty to repair lost or damaged dura. Collagen-based dura substitutes are mainstream products in both the US and Chinese markets. In this study, dura substitute devices with potential dura regeneration ability are evaluated. The dura substitutes are composed of fibrous type I collagen that were purified from bovine tendon. Physical and chemical characterization demonstrated that the tested dura substitute has desirable porous scaffolding structures and is composed of highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…[72] Moreover, glycerol interaction with collagen is important in the context of the suitability of the collagenous tissue as a dural graft in the repair of spinal dura mater defects. [73, 74]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[72] Moreover, glycerol interaction with collagen is important in the context of the suitability of the collagenous tissue as a dural graft in the repair of spinal dura mater defects. [73, 74]…”
Section: Resultsmentioning
confidence: 99%
“…[72] Moreover, glycerol interaction with collagen is important in the context of the suitability of the collagenous tissue as a dural graft in the repair of spinal dura mater defects. [73,74] The inherently weak Raman scattering efficiency and the high scattering of the turbid tissue limits CRM use to superficial layers. To overcome this lack and to extend Raman scattering probing to deeper tissues by using optical clearing method with the assistance of metallic nanoparticles can be further used.…”
Section: Discussionmentioning
confidence: 99%
“…According to our clinical data, we consider that severe TBI patients are more likely to benefit from biological suturable nonabsorbable dura with good airtightness and elasticity for dura repair in DC. However, sutureless absorbable dura also has its advantages of small patches application in some locations difficult to reach, shorter surgery duration and better histomorphologic outcomes (45)(46)(47). A recent study reported a new absorbable dura made of Poly L Lactic Acid which shows good mechanical properties and represents better anti-adhesive property than NormalGEN in preclinical studies (48).…”
Section: Discussionmentioning
confidence: 99%
“…It is made up of fibrous tissue, including collagenic and elastic fibers, and functions as a barrier to contain cerebrospinal fluid (CSF) within the cranial cavity. The dura mater can be divided into two layers [ 50 , 51 ]. The dense inner layer of the dura mater is the meningeal dura, which serves as a barrier by preventing the leakage of CSF and adhesion of brain tissue, guarding against superficial cerebral infection, and maintaining intracranial pressure.…”
Section: Biomedical Applications Of Electrospun Nanofibersmentioning
confidence: 99%